Hambatan Sosial Budaya dalam Pencegahan Anemia pada ibu Hamil: Studi Fenomenologis di Wilayah Lombok Timur, NTB - Safinatunnaja, Bq.; Mawaddah, Shohipatul; Mutianingsih, Rosa (JIKF, 2025)
Anemia during pregnancy remains a significant public health issue in Indonesia, including in West Nusa Tenggara Province. Despite various intervention efforts, such as the distribution of Iron and Folic Acid (IFA) tablets, the prevalence of anemia remains high. This study aims to explore the socio-cultural barriers faced by pregnant women in preventing anemia, particularly in East Lombok Regency, using a qualitative phenomenological approach. Data were collected through in-depth interviews, participatory observations, and document reviews, and analyzed using a thematic interpretative approach based on the Health Belief Model (HBM). The findings indicate that low risk perception, limited understanding of the dangers of anemia, physical and cultural barriers to IFA tablet consumption, and lack of support from families and healthcare providers are the main factors influencing anemia prevention behavior. This study recommends the need for a contextual education approach rooted in local cultural values, as well as the active involvement of community leaders and family members in promoting maternal health.